Determination of Total Phenolic Content, Analysis of Bioactive Compound Components, and Antioxidant Activity of Ethyl Acetate Seri (Muntingia calabura L.) Leaves from North Sumatera Province, Indonesia - Situmorang, Risanti Febrine Ropita; Gurning, Kasta; Kaban, Vera Estefania; Butar-Butar, Mastiur Julianti; Perangin-Angin, Susi Amenta Beru (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Seri (Muntingia calabura L.) leaves are a plant that is often found and have not been used in various treatments even though it is reported to have various groups of bioactive compounds such as phenolic, flavonoids, tannins, saponins, steroids, and triterpenoids. AIM: This study aimed to determine the total phenolic content, antioxidant activity and identify the content of potential bioactive compounds contained in the ethyl acetate fraction from M. calabura leaves. METHODS: M. calabura L. leaves fraction was carried out by maceration method using ethanol followed by partition starting with n-hexane, chloroform, and finally ethyl acetate as solvent. The ethyl acetate fraction was continued for phytochemical screening for the content of bioactive compounds using standard reagents, determination of total phenol content by colorimetric method, determination of antioxidant activity using the DPPH method, and analysis of bioactive compounds using gas chromatography–mass spectroscopy. RESULTS: The results showed that the ethyl acetate fraction of M. calabura leaves was positive for phenolic content which was indicated by the formation of a turquoise color after 5% FeCl3 reagent was added (in ethanol), phenolic content was 0.0727 mg GAE/g dry fraction, indicating antioxidant activity (IC50) amounted to 54.437 including strong categories as antioxidants and the results of GC–MS analysis obtained various kinds of compounds and it is suspected that compounds that provide potential as antioxidants are phytol. CONCLUSION: The bioactive compound of ethyl acetate fraction of seri (M. calabura) leaves contained phenolic components and has strong antioxidant activity.